2018
DOI: 10.1029/2018jf004608
|View full text |Cite
|
Sign up to set email alerts
|

Submarine Deposition of a Subaerial Landslide in Taan Fiord, Alaska

Abstract: A large subaerial landslide entered Taan Fiord, Alaska, on 17 October 2015 producing a tsunami with runup to 193 m. We use LiDAR data to show the slide volume to be 76 + 3/−4 million cubic meters and that 51,000,000 m3 entered Taan Fiord. In 2016, we mapped the fjord with multibeam bathymetry and high‐resolution seismic data. Landslide and postlandslide deposits extend 6 km downfjord, are up to 70 ± 11 m thick, and have a total volume of ~147,000,000 m3. Seismic data image a blocky landslide unit and two units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…In the case of the summer 2016 Aru twin glacier collapse (Kääb and others, 2018), the seismically inferred total mass was a factor of three to six lower than the avalanche deposit volumes derived from DEMs (see their supplementary text S10). Conversely, both methods agreed reasonably well on the total mass of rock mobilized (1-1.5 × 10 11 kg for the seismic method, 1.8 × 10 11 kg for the DEM differencing) during the 2015 Taan Fiord rock avalanche in the Gulf of Alaska (Haeussler and others, 2018;Higman and others, 2018). The seismic approach is thus efficient to precisely date the avalanche (Jiskoot, 2011), capture the sequence of events (Ekström and Stark, 2013) and locate them geographically (Higman and others, 2018) but needs to be combined with satellite imagery and DEMs for a more reliable estimate of the mass displacement.…”
Section: Comparison To Mass Balances From Earlier Studiesmentioning
confidence: 78%
“…In the case of the summer 2016 Aru twin glacier collapse (Kääb and others, 2018), the seismically inferred total mass was a factor of three to six lower than the avalanche deposit volumes derived from DEMs (see their supplementary text S10). Conversely, both methods agreed reasonably well on the total mass of rock mobilized (1-1.5 × 10 11 kg for the seismic method, 1.8 × 10 11 kg for the DEM differencing) during the 2015 Taan Fiord rock avalanche in the Gulf of Alaska (Haeussler and others, 2018;Higman and others, 2018). The seismic approach is thus efficient to precisely date the avalanche (Jiskoot, 2011), capture the sequence of events (Ekström and Stark, 2013) and locate them geographically (Higman and others, 2018) but needs to be combined with satellite imagery and DEMs for a more reliable estimate of the mass displacement.…”
Section: Comparison To Mass Balances From Earlier Studiesmentioning
confidence: 78%
“…Several studies have documented landslides in the study area during the past century. Most recently, in October 2015 the Taan Fiord landslide (Dufresne et al, 2018;Haeussler et al, 2018;Higman et al, 2018) involved the collapse of 76 Mm 3 of material (Haeussler et al, 2018) from a previously identified, unstable mountain flank (Meigs and Sauber, 2000), onto the terminus of Tyndall Glacier and into Taan Fiord. This landslide generated a tsunami with a maximum onshore runup of 193 m (Higman et al, 2018).…”
Section: Study Areamentioning
confidence: 99%
“…understanding of the preconditioning factors, frequency and dynamics of these events is very important. In 2015 in Taan Fjord, Alaska, a 0.147 km 3 rockfall generated a large tsunami, fortunately with no casualties (Haeussler et al, 2018). The tsunami runup from this event was an astounding 193 m, making it among the largest ever recorded (Higman et al, 2018).…”
Section: Glacial Alpine Environments -Locus Of Climate Sensitivitymentioning
confidence: 99%
“…The tsunami runup from this event was an astounding 193 m, making it among the largest ever recorded (Higman et al, 2018). Post-event mapping has enabled a detailed calculation of the scale of the deposit, and the characteristics of the source area (Dufresne et al, 2018;Haeussler et al, 2018). It is likely that landslides in glaciated areas will become more frequent as the climate changes and glaciers retreat (Grämiger et al, 2017).…”
Section: Glacial Alpine Environments -Locus Of Climate Sensitivitymentioning
confidence: 99%